Sense of Coherence in Healthcare Workers During the COVID-19 Pandemic in Ecuador: Association With Work Engagement, Work Environment and Psychological Distress Factors - Juan Gómez-Salgado; Juan Gómez-Salgado; Cristian Arturo Arias-Ulloa; Mónica Ortega-Moreno; Juan Jesús García-Iglesias; Kenny Escobar-Segovia; Carlos Ruiz-Frutos; Carlos Ruiz-Frutos (Frontiers Media S.A., 2022)
Objectives: The aim of this study was to test the association between the sense of coherence, work engagement, and psychological distress in healthcare workers in Ecuador during the first phase of the COVID-19 pandemic.Methods: A cross-sectional observational study in a sample of 803 healthcare professionals from all regions of Ecuador between 2 April and 17 May 2020. A self-administered questionnaire was used, which contained sociodemographic and work environment variables, the Utrecht Work Engagement Scale (UWES-9), the General Health Questionnaire (GHQ-12), and Sense of Coherence Scale (SOC-13).Results: The mean value of sense of coherence was M = 65.04; SD = 12.74; for work engagement, it was M = 39.36; SD = 10.53; and for psychological distress, M = 4.58; SD = 3.44. There is a positive correlation (p < 0.01) between the sense of coherence and work engagement, and a negative correlation with psychological distress.Conclusion: During the pandemic in Ecuador, healthcare professionals have suffered a major deterioration of their mental health. Sense of coherence has been associated with work engagement and psychological distress. They have perceived a worsening of the quality of care and working conditions compared to those existing before COVID-19.